La interdisciplinaridad como estrategia de aprendizaje para integrar los contenidos de las ciencias naturales en los estudiantes de octavo año de educación general básica de la Unidad Educativa Amelia Gallegos Díaz, Periodo Abril –Junio 2017 - Chunata Inca, Silvia Elizabeth (2017)
The research work was focused on establishing whether interdisciplinary as a learning methodology integrated the contents of the natural sciences in the eighth grade students of Basic General Education at Amelia Gallegos Diaz, Educational United April-June 2017.Interdiciplinary could be seen as a pedagogical strategy that implied the interaction of several persuasions, assumed as the dialogue and the collaboration of these to achieve the goal of a new knowledge, in the study showed that the teachers did not know the interdisciplinary as a strategy of interaction and crossings of disciplines that implied a Maximum level of unification therefore interdisciplinary fosters a learning from an interdisciplinary approach with approach with appropriate didactic materials and the updating of the permanent teacher, which leaded to the development of the didactic skills and the acquisition of disciplinary knowledge to imp This new form of education was successfully established. The methodology of the work was based on the documentary and field design, its level was diagnostic and descriptive. For the collection of the information was used the technique of the survey with its instrument the questionnaire, applied the sample to thirty seven students. In conclusion, interdisciplinary tried to find, establish, organize and manage each of the knowledge that is organized in fragmented disciplines that were present in each one of the disciplines .It also promoted cooperation and exchange relationships, as well as a critical analysis and reconsidering to search the knowledge. It was recommended to promote interdisciplinary as a method of learning since it contributed to the development of reflection and analysis around their own actions, resolution of personal and group conflicts and approach to the construction of knowledge.